Pembelajaran PAI Berbasis Bahasa Inggris Sebagai Upaya Menghadapi Tantangan Globalisasi di MI Afkaaruna Islamic School Yogyakarta - Astri Khoirunnisa (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2021)
Today, society is faced with the phenomenon of globalization. This is immediately give demands that need more attention from all levels of society. The existence of globalization causes several challenges including self-defense to face global phenomena, self-readiness to face the era of competition, and readiness to improve self quality as a qualified human resource. It can be accomplished through educational reforms and creating new innovations in education. English-based Islamic Religious Education Learning is expected to be one of the way to prepare students to face the challenges of globalization. This research aims to find out how English-based learning of Islamic Religious Education is one of the way to face the challenges of globalization. The research is conducted on grade I students of MI Afkaaruna Islamic School Yogyakarta. This research used descriptive-qualitative research methode. The results of this study can be concluded that English-based Islamic religious education learning can be used as one of the way to prepare students to face the challenges of globalization because of the many benefits that are relevant as the solution for this matter.